Patients with multiple sclerosis present low levels of empathy - Almeida, Marcos Barbosa de; Going, Luana Carramilo; Fragoso, Yara Dadalti (Arquivos de Neuro-Psiquiatria, 2016)
Multiple sclerosis (MS) is a chronic neuroimmunological disease that mainly affects young adults, leading to neurological disabilities over the course of their lives. Many psychiatric conditions have been reported in patients with MS, but there are remarkably few studies assessing empathy among these patients. This is a single center, cross-sectional study, of 34 patients with MS and 34 matched control subjects. A specific questionnaire (empathy quotient) was used.Patients with MS showed significantly lower levels of empathy. This finding was not correlated with disease duration, degree of disability, drugs for treating MS or lesion load on resonance magnetic imaging.Decreased empathy is a frequent condition in patients with MS and should be addressed in order to diminish the psychosocial burden of this neurological disease.
Keywords: empathy; multiple sclerosis; psychology